Mobile Market Research Applications as a New Voice of Customer Method: Implications for Innovation and Design Management. Issue 1 (2nd January 2020) - Green, William; Cluley, Robert; Gasparin, Marta
Abstract : Overview: This paper describes mobile market research applications (MMRAs), new Voice of the Customer (VoC) tools that take advantage of the ubiquity of smartphones. MMRAs provide an efficient and effective method of collecting intimate, in situ data from customers, allowing traditional VoC approaches to be augmented with digitally captured data. MMRAs can thus reduce ambiguity in the fuzzy front end of the innovation process by providing access to data from likely customers from the earliest stages of exploration. To benefit from MMRAs, however, organizations must move beyond a traditional mindset: the adoption of an MMRA requires teams to be restructured and projects reorganized to accommodate the new methods enabled by the tools.